THE DETERMINANTS OF A SUCCESSFUL IMPLEMENTATION OF E-RETRIBUTION PAYMENT SYSTEM: EVIDENCE FROM SLIPI MARKET OF JAKARTA - Prabowo, Ilham Condro; Marwah, Syafa Kamilla (Bina Nusantara University, 2023)
Payment of market retribution using E-Retribution makes it easier for traders in the market to settle their obligations. This study aims to determine the factors that influence the success of implementing E-Retribution using the Delone & Mclean IS Success Model. The present study used primary data using a questionnaire. Respondents to this study were 96 traders who used E-Retribution at Slipi Market, West Jakarta, by selecting using a purposive sampling method. The data analysis method used is PLS-SEM. The findings demonstrated that system, information, and service quality substantially impacted user satisfaction. However, system quality did not impact use, but the information and service quality significantly impacted use. After then, net benefits were significantly impacted by both use and user satisfaction.